Análise dos efeitos das mudanças de uso do solo em zonas de recarga do Aquífero Botucatu: estudo de caso em São Carlos – SP - Ruggiero, Mayara Herrmann (2017)
The groundwater is a resource of which many countries are dependent for the water supply of the population, being the maintenance of these reserves necessary. The anthropic activities can cause the commitment of the water supply. These activities result in changes on the landscape natural patterns, altering the land use. In this regard, there is the need to evaluate if the kind of land use in a region affects the groundwater recharge, and which activities can compromise in the future the aquifers supply. As such, the objective of this study was analyze the changes in land use on the recharge zone of the Botucatu Aquifer and how these changes affects the potential capacity of water infiltration in the ground and increase the local contamination potential. To this end, for the accomplishment of this research, the Chibarro and Ribeirão do Feijão watersheds were selected, located in the São Carlos municipality. First of all, a bibliographic review about this subject was made, followed by a multitemporal analysis of the land use, using the years of 1985, 2000 and 2015, using the Land Change Modeler of IDRISI software. Thus, the land cover scenarios for 2030 were projected, and it was made aquifer vulnerability maps using the DRASTIC methodology and the Susceptibility Index. The next step was the elaboration of maps of the infiltration potential capacity, trough the connection between the local geological materials and land cover. The results showed that both watersheds report trends of urban growth. In Chibarro watershed there was an increase of natural vegetation, while in Ribeirão do Feijão watershed there was a decrease. The vulnerability maps showed that the land use in both areas exercising pressure upon the aquifer may cause contamination. The infiltration potential capacity maps showed that in both watersheds is possible to happen the decrease of this capacity, risking the aquifer recharge.